RANCANG BANGUN SISTEM PENGAMBILAN CITRA DAN PENGATUR POSISI JARAK OBYEK PADA MIKROSKOP DIGITAL MENGGUNAKAN JARINGAN WiFi SMARTPHONE ANDROID BERBASIS RASPBERRY Pi 3 DAN MIKROKONTROLER ESP32 - Putranto, Ari Bawono; Baital, Muhammad Sawal; Muhlisin, Zaenul; Adi, Kusworo (BERKALA FISIKA, 2020)
In this study, the ESP32 microcontroller and the Raspberry Pi have been successfully combined to adjust the position of the digital microscope object and take images using an android smartphone-based application via a WiFi network. The working method of adjusting the position of the microscope object is done by using the number of steps on a unipolar stepper motor starting from the farthest distance to the digital microscope objective lens which is regulated by the ESP 32 microcontroller. Meanwhile, viewing the microscope object directly can be done via a mobile screen connected to a WiFi network to a digital microscope USB camera that has been converted into an IP camera by the Raspberry Pi. Therefore, through the use of a digital microscope application with an Android smartphone, it will be easier to obtain a sample image of a digital microscope object when conducting experiments in the laboratory.Keywords: Digital Microscope, Android Smartphone, WiFi, Rsabperry Pi, Microcontroller ESP 32